2008
DOI: 10.4238/vol7-3gmr475
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mutagenicity effects of Psidium cattleyanum Sabine (Myrtaceae) extract on peripheral blood and bone marrow cells of mice

Abstract: AbSTrACT. Cattley guava (Psidium cattleyanum Sabine) is a native fruit of Brazil that is popular both as a sweet food and for its reputed therapeutic properties. We examined whether it could damage DNA using the alkaline single-cell gel electrophoresis (comet assay) and the micronucleus test in leukocytes and in bone marrow cells of mice. P. cattleyanum leaf extract was tested at concentrations of 1000, 1500 and 2000 mg/kg. N-nitroso-N-ethylurea was used as a positive control. Peripheral blood leukocytes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…Our in vivo results revealed that the three doses that were used did not induce DNA damage; instead, the level of DNA damage that was induced by the extract showed significant differences (P < 0.05) compared with the positive control. Similar results were obtained by Costa et al (2008) and Magalhães et al (2010), who used the comet assay to study extracts of Psidium cattleianum Sabine (Myrtaceae) and Ilex paraguariensis (Aquifoliaceae), respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Our in vivo results revealed that the three doses that were used did not induce DNA damage; instead, the level of DNA damage that was induced by the extract showed significant differences (P < 0.05) compared with the positive control. Similar results were obtained by Costa et al (2008) and Magalhães et al (2010), who used the comet assay to study extracts of Psidium cattleianum Sabine (Myrtaceae) and Ilex paraguariensis (Aquifoliaceae), respectively.…”
Section: Discussionsupporting
confidence: 81%
“…1a e 1b). Comparativamente, Costa et al (2008) observou que a mistura de compostos presentes nos extratos das folhas de P. cattleianum não apresentaram efeitos mutagênicos em alguns tipos de células in vivo de Mus musculus.…”
Section: Tratamentosunclassified
“…Teixeira et al [19] demonstrated that P. guajava infusion does not alter chromosomes or the cell cycle both in vitro and in vivo. Costa et al [20] show that P. cattleianum leaf extract does not have any genotoxic or mutagenic effects on some cell types of mice, suggesting that this extract can be used as a safe therapeutic agent. The crude ethanolic extract of the plant was obtained through maceration and fractionated with hexane, dichloromethane, and ethyl acetate for test in microcrustacean Artemia salina for toxicological assessment.…”
Section: Toxicity Of P Cattleianummentioning
confidence: 99%